Financial Review of Gillnet Fishermen's Joint Business Group (KUB) in Beach South West (BARSELA) Aceh - M Rizal; budi wiryawan; sugeng h wisudo; iin solihin (Faculty of Fisheries and Marine Science, Brawijaya University, 2017)
Production of marine fisheries in Barsela over the last five years, based on capture fisheries statistical data of Aceh province, has increased to 285,926.6 tonnes in 2010-2014. Therefore, the total production will affect fishing effort and the fishermen (DKP 2010-2014). The increasing factors of the number of fishing fleet in every year followed by the increasing of fish production still cannot increase the income and welfare of fishermen, particularly the joint business group (KUB) of gillnet fishermen whom are categorized as small-scale fishermen. This study aims to analyse the feasibility of gillnet fishermen's KUB in the area of Barsela Aceh. The result showed that KUB of gillnet fishermen is feasible to continue an average profit of Rp 58.878621. The value of R/C is > 1 with an average value of 1.50. The value of average PP is 1,49 (18 months) to restore the stock. The feasibility of business investment of gillnet fishermen's KUB obtained NPV value > 1, with the average value of 51.951.818, the value of Net B/C is > 1 with an average value of 1.73 and IRR values with an average value of 54%, higher than interest rate level (14%) so that it can be concluded that the JBG of gillnet fishermen is feasible to continue.